Synthesis of Pyridoacridines through Anionic Cascade Ring Closure - Petersen, Ida Nymann; Kristensen, Jesper Langgaard (Synthesis, 2014)
A new synthesis of 13-deazaascididemin (AK-37) based on a recently developed anionic cascade ring closure is presented. Although the isolated yields are modest, the approach provides ready access to new substituted derivatives of 13-deazaascididemin.
Keywords: fused ring systems; natural products; cross coupling; anionic cascade ring closure; oxidation